2014
DOI: 10.1007/s00453-014-9884-6
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Performance Measures for Online Algorithms

Abstract: This paper provides a systematic study of several proposed measures for online algorithms in the context of a specific problem, namely, the two server problem on three colinear points. Even though the problem is simple, it encapsulates a core challenge in online algorithms which is to balance greediness and adaptability. We examine Competitive Analysis, the Max/Max Ratio, the Random Order Ratio, Bijective Analysis and Relative Worst Order Analysis, and determine how these measures compare the Greedy Algorithm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…In terms of a direct comparison of online algorithms, we obtain that greedy has a bijective ratio of at most 2k/3 against k-Center. It is worth mentioning that our results expand the work of Boyar et al [16] who showed that greedy is bijectively optimal for the 2-server problem on a very simple, albeit discrete metric consisting of three colinear points (termed the baby server problem).…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…In terms of a direct comparison of online algorithms, we obtain that greedy has a bijective ratio of at most 2k/3 against k-Center. It is worth mentioning that our results expand the work of Boyar et al [16] who showed that greedy is bijectively optimal for the 2-server problem on a very simple, albeit discrete metric consisting of three colinear points (termed the baby server problem).…”
Section: Introductionsupporting
confidence: 80%
“…Boyar et al [16] provided a systematic study of several measures for a simple version of the k-server problem, namely, the two server problem on three colinear points. In particular, they showed that greedy is bijectively optimal.…”
Section: Related Work and Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…For completeness, we include these results. Random order analysis [20] was introduced for classic bin packing, but has also been used for other problems; a server problem, for instance [8]. Max/max analysis [3] was introduced as an early step towards refining the results from competitive analysis for paging and a server problem.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic comparison of performance measures for online algorithms was initiated in [24], comparing some measures which are applicable to many types of problems. To make this feasible, a particularly simple problem was chosen: the 2server problem on a line with three points, one point farther away from the middle point than the other.…”
Section: Comparisons Of Performance Measuresmentioning
confidence: 99%